DEVELOPMENT OF A TECHNOLOGY FOR PRODUCING A STABLE INJECTABLE DOSAGE FORM OF A HYDROPHOBIC INDOLOCARBAZOLE DERIVATIVE - DMITRIEVA, MARIA; KOLPAKSIDI, ALEXANDER; ORLOVA, OLGA; IGNATYEVA, ELENA; LANTSOVA, ANNA; NIKOLAEVA, LUDMILA; KRASNYUK, IVAN (International Journal of Applied Pharmaceutics, 2021)
Objective: Development of a technology for the production of a stable injectable dosage form (IDF) of indolocarbazole derivative LHS-1269. Methods: LHS-1269 is an active pharmaceutical ingredient that was synthesized in the N. N. Blokhin National Medical Research Center of Oncology of the Ministry of Health of the Russian Federation. The IDF includes dimethyl sulfoxide (DMSO), 95% ethanol, Kollidon® 17PF and water for injection. Magnetic stirrer and overhead stirrer with a propeller stirring element were used to prepare the model solution of the IDF of LHS-1269. Sterilizing filtration of the solution was performed with 0.2−0.22 um polycarbonate, cellulose, polyvinylidene fluoride, polyethersulfone and nylon membrane filters. The aqueous solution of LHS-1269 was lyophilized in Edwards Minifast DO.2 freeze dryer. Assay of LHS-1269 was performed by spectrophotometry at 320±3 nm. Potentiometry was used to measure pH, a viscosimetry method was used to measure the viscosity of the solutions. The average weight was estimated by weighing a sample of 10 vials with the concentrate. Results: 0.5% aqueous solution of LHS-1269 was produced by mixing the solution of the active substance in DMSO and ethanol with an aqueous solution of polyvinylpyrrolidone gradually at the ratio of LHS-1269/DMSO/ethanol/Kollidon® of 1/11/32/40 by weight. The aqueous solution of the study substance cannot be lyophilized, so a sequence of technological operations was presented to produce an anhydrous concentrate “LHS-1269, concentrate for solution for injection and infusion 25 mg”. Conclusion: A technology was developed to produce a stable IDF of a hydrophobic indolocarbazole derivative LHS-1269, a high-potential antitumor drug.